DIVIDEND POLICY, PROFITABILITY AND CAPITAL TOWARDS BANKING VALUE - Ernawati Ernawati; Nugraha Nugraha; Maya Sari (Program Studi Magister Manajemen FE Unsri, 2020)
ABSTRACTResearch purpose – This study aims to test the influence of dividend policy, profitability, and capital on banking value. This research was conducted on banking financial sector companies included in the Indonesia Stock Exchange LQ45 index for the period 2015-2019. Methods – Samples were selected using a non-probability sampling method with purposive sampling. Data analysis with multiple linear regression techniques. Result – The results showed that dividend policy has no significant influence on the value of the company. Banking profitability also has no influence on the value of the company. Meanwhile, banking capital has a positive and significant influence on the company's value. The success of the company depends largely on the company's ability to raise capital, because insufficient capital will hinder the development of the company. Banking capital that continues to increase above the average banking standard shows the ability of banking capital is very good, this means that the ability of existing capital in the banking system is able to cover possible losses in credit activities and trading of banking securities. Limitations of research - There are two proxies, dividend policy and profitability policies that have not given evidence of the company's value and the small value of R2 is the material for further research. Originality - This study discusses the function of financial management as measured by financial decisions, and discussions on banks listed in LQ45 with variable testing separately.